PM2.5-induced extensive DNA methylation changes in the heart of zebrafish embryos and the protective effect of folic acid. (December 2019) - Jiang, Yan; Li, Jianxiang; Ren, Fei; Ji, Cheng; Aniagu, Stanley; Chen, Tao
Abstract: We previously found that folic acid (FA) attenuated cardiac defects in zebrafish embryos exposed to extractable organic matter (EOM) from PM2.5, but the underlining mechanisms remain to be elucidated. Since DNA methylation is crucial to cardiac development, we hypothesized that EOM-induced aberrant DNA methylation changes could be diminished by FA supplementation. In this study, zebrafish embryos were exposed to EOM in the absence or presence of FA. Genomic-wide DNA methylation analysis identified both DNA hypo- and hyper-methylation changes in CCGG sites in zebrafish embryos exposed to EOM, which were attenuated by FA supplementation. We identified a total of 316 genes with extensive DNA methylation changes in EOM samples but little or no DNA methylation changes in EOM plus FA samples. The genes were involved in critical cellular processes and signaling pathways important for embryo development. In addition, the EOM-decreased SAM/SAH ratio was counteracted by FA supplementation. Furthermore, FA attenuated the EOM-induced changes in the expression of genes involved in the regulation of DNA methylation and in folate biosynthesis. In conclusion, our data suggest that FA supplementation protected zebrafish embryos from the cardiac developmental toxicity of PM2.5 by alleviating EOM-induced DNA methylation changes. Graphical abstract: Image 1 Highlights: FA protected against heart defects induced by EOM from PM2.5. FA alleviated EOM-induced DNA methylation changes. FA counteracts the decreased SAM/SAH ratio caused by EOM. FA attenuated the EOM-induced gene expression changes. Abstract : Main finding of the work: EOM from PM2.5 induced dramatic DNA methylation changes in the heart of zebrafish embryos, which was significantly attenuated by folic acid.